A tradable permit systems for the control of pollution of firms with waste water discharges to the sewerage network - Méndez Sayago, Johanna Mildred; Méndez Sayago, Jhon Alexander (Sociedad y Economía, 2010)
In this paper is proposes a tradable permit systems for the control of pollution from industrial and commercial users with waste water discharges to the sewerage network to the sewerage network. This system in conjunction with a scheme of individual and collective sanctions has the ability to induce socially efficient behavior in firms that generate waste water, i.e. can achieve a goal of contamination at the lowest cost. The proposal is different from the current instrument of retributive rates for the control of pollutants with discharges on bodies of water, whose regulation and implementation does not conducive to the principle of cost effectiveness in pollution control for these users.